Thirty-Seventh Annual Homecoming Pope's Chapel United Methodist Church, October 3, 1993 - (:unkn) unknown (Pope's Chapel United Methodist Church (Wilkes County, Ga.))
Thirty-Seventh Annual Homecoming Pope's Chapel United Methodist Church, October 3, 1993. Robert L. Reynolds, Jr., Pastor. Event program. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_19931003.pdf. 4 pages. 24555482 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Asbury, Francis; Bamford, Sophia; Bohler, Eugenia; Boyd, Gail; Boyd, James W.; Boyd, John W.; Boyd, John Wright; Boyd, Misha; Boyd, Shana; Boyd, Tonya; Boyd, Whitney; Bunch, Linda; Cash, M. T.; Chafin, David; Chafin, Elizabeth; Chafin, Malcolm; Combs, Farmer; Combs, Hazel; Fortson, Benjamin Winn; Gibson, Marjorie; Harris, Lundye; Humphries, Thomas; Keen, John; Keen, Rhonda C.; Landrum, John; Lawrence, Harold; Lawrence, Linda; Neal, Augustus A.; Ogilvie, Hannah Rebecca; Pope, Henry; Pullen, Thomas B.; Reynolds, Robert L.; Sale, David; Wheatley, Jimmy; Wheatly, Elaine; Wiggins, Tom